Physical and sensory properties of meltique beef steak injected with virgin coconut oil emulsion - Apriantini Astari; Cipta Dainy Nunung; Humayrah Wardina; Nurzahra Kania; Lesa Aditia Edit (BIO Web of Conferences)
The consumption of animal-based protein in Indonesia remains low, necessitating efforts to increase its intake, particularly through beef. Beef contains complete nutrition content such as essential amino acids, vitamins and minerals (Fe, Zn). However, its thick muscle fibers, make it less tender and more difficult to consume. One potential innovation to improve beef tenderness is the injection of plant-based oil, which results in meltique beef. This study aims to investigate the physical and sensory characteristics of meltique beef injected with Virgin Coconut Oil (VCO) emulsion as a source of animal protein. This study employed a completely random design. Sensory evaluation was conducted using the hedonic test and sensory attribute profiling technique with 25 initiated panellists. Meltique beef injected with VCO emulsion demonstrated the same quality of physical and sensory characteristics comparable to those of wagyu beef and canola oil emulsion in terms of texture, tenderness, and oil content. Therefore, VCO emulsion-injected meltique beef can serve as a preferred and easily consumable protein source due to its soft texture and affordable prices.